2004
DOI: 10.1038/sj.ejcn.1601888
|View full text |Cite
|
Sign up to set email alerts
|

The effect of docosahexaenoic acid-containing food administration on symptoms of attention-deficit/hyperactivity disorder—a placebo-controlled double-blind study

Abstract: We recently reported 'The effect of docosahexaenoic acidcontaining food administration on symptoms of attentiondeficit/hyperactivity disorder-a placebo-controlled doubleblind study ' (Hirayama et al, 2003). In that study, aggression of AD/HD schoolchildren was rated with our original questionnaire to their parents and teachers, and counted only when both of them gave the same assessment, like the method of AD/HD-related symptoms criteria of DSM-IV. However, the method of counting only when both of them agreed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…The authors of that study suggested that DHA might depress the brain noradrenergic system taking into account that attention of AD/HD children was not improved. The careful reevaluation of that study revealed that aggression (including physical aggression), the sum of the scores rated separately by parents and teachers, was significantly reduced in the DHA group compared with the control group [20]. Norepinephrine is related with aggression [21].…”
Section: Discussionmentioning
confidence: 96%
“…The authors of that study suggested that DHA might depress the brain noradrenergic system taking into account that attention of AD/HD children was not improved. The careful reevaluation of that study revealed that aggression (including physical aggression), the sum of the scores rated separately by parents and teachers, was significantly reduced in the DHA group compared with the control group [20]. Norepinephrine is related with aggression [21].…”
Section: Discussionmentioning
confidence: 96%
“…If anything, there was an improvement of visual and auditory memory in placebo relative to DHA group. Subsequent recalculation of aggression in the 2 groups by taking into consideration the ratings by parents and the ratings by teachers separately revealed that the DHA intervention resulted in significantly reduced aggression as compared to placebo [165]. This beneficial effect of DHA treatment may have important implications for the social behavior of ADHD children.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 92%
“…Hirayama et al [7] found that supplementation of 0.61 g of LC omega-3 fatty acids per day for two months (primarily DHA in foods) had no effect when analyzing parent and teacher assessments separately in children with ADHD; however, when analyzing assessments together, physical aggression significantly improved compared to the placebo group [8]. Voigt et al [9] supplemented children with ADHD for four months with 0.35 g of DHA per day and found no improvements in any ADHD symptoms.…”
Section: Introductionmentioning
confidence: 99%